BAKTI SOSIAL TARUNA-TARUNI AKADEMIK AKADEMI MARITIM NUSANTARABANJARMASIN DALAM MENINGKATKAN KESADARAN PENTINGNYA PEDULI BERSIH DI LINGKUNGAN PANTAI TAKISUNG BANJARMASIN - M. Firdaus Suwestian; Hadiansyah; Veby Senopati Silam; Prihatin; Irtania (Akademi Maritim Nusantara Banjarmasin, 2022)
AbstractSocial activities are caring for other people who do have limitations. Social activities also vary, suchas social services or social activities that are often carried out by corporations with free health checks, theCampagne movement to defend a group. Social assistance is one of the activities that manifests humanity amonghuman beings. Social Service is an activity where with this activity we can strengthen our kinship, to manifest asense of love, mutual help, mutual concern for students to the wider community who are in need of their helpinghand. The purpose of holding community social service activities is to increase awareness and a social sense of thecondition of rural communities which are increasingly apprehensive, both in terms of economic needs and interms of employment, creating people who care about others, giving motivation to the community about theimportance of awareness in increase insight. Order of social life in the community will be orderly and balanced ifdecorated with a high sense of solidarity.This activity method is carried out at the beginning of the new school year in 2022 in September, aswell as the activities of cadets in physical and spiritual activities outside the campus environment in applyingphysically, mentally and socially to the community. This implementation is in the form of activities in the field,namely by carrying out the theme of social service activities for the Academic Community of the BanjarmasinArchipelago Maritime Academy in the community around the Banjarmasin Batakan coast. The socializationmethod is carried out in two main parts, namely presentation of material and case studiesThe results of the community service activities carried out on the batakan beach with theBanjarmasin Nusantara Maritime Academy, namely Establishing Communication and Gathering ThroughService Activities in the form of debriefing the community around the batakan beach so that residents have anunderstanding of the environment by having an understanding of the impacts and benefits of caring forcleanliness and handling disasters quickly so that they have an impact directly to the local economy.Keywords. social service, clean care, beach